Toward a Legally Interoperable NFT Ecosystem: A Hybrid Framework for Intellectual Property Governance in Digital Assets - Luo, Bixiao (Studies in Law and Justice, 2025)
This paper investigates the unresolved intellectual property challenges posed by non-fungible tokens (NFTs), a rapidly growing class of digital assets that blend decentralized technologies with creative content distribution. Despite widespread adoption across art, entertainment, and gaming sectors, the legal infrastructure surrounding NFTs remains fragmented, creating uncertainty for creators, buyers, and platforms alike. The objective of this study is to critically evaluate existing theoretical models—including property-based, contract-based, and provenance-centered approaches—and assess their adequacy in governing NFT-related rights and obligations. Methodologically, the paper employs a comparative legal analysis of current NFT licensing practices, supported by interdisciplinary review of blockchain architecture, smart contract functionalities, and relevant international IP frameworks. Based on legal theory, technical standards, and case studies, the paper identifies critical gaps in enforceability, rights attribution, and jurisdictional clarity. In response, the study proposes a hybrid legal-technical framework comprising seven interconnected components: Smart Licensing Infrastructure (SLI), an On-Chain Provenance and Rights Registry, Embedded Royalty Clauses with Legal Backing, Token-Linked Legal Contracts (TLCs), along with dispute resolution and jurisdictional compatibility. These elements collectively aim to bridge decentralized code execution with enforceable legal standards, facilitating clearer licensing arrangements, more reliable royalty enforcement, and scalable dispute resolution mechanisms. It presents a novel blueprint for technical capabilities of NFTs with the foundational requirements of intellectual property law. By incorporating legal metadata, verifiable authorship records, and jurisdictional parameters directly into NFT structures, the framework strengthens legal predictability without restricting innovation. This research contributes to academic discourse by advancing a multidimensional governance approach for digital assets, offering actionable pathways toward regulatory coherence and sustainable development within the NFT ecosystem moving forward.